The Influence of Organizational Commitment, Effective Communication, and the Work Environment on the Caring Behavior of Inpatient Nurses at Annisa Hospital, Cikarang - Rahmadiyanto, Sashenna; Aziz, Abdul; Istiqlal, Haidar (IJBLE Scientific Publications Community Inc., 2025)
Nurses’ caring behavior in providing nursing care to patients plays a crucial role in enhancing the quality of nursing services and ensuring patient safety, which in turn contributes to patient recovery. However, in practice, the delivery of high-quality nursing services is still hindered by the prevalence of non-caring behaviors in patient care. Therefore, concrete measures are required to reduce such behaviors by strengthening organizational commitment, effective communication, and the work environment, thereby fostering caring behavior among nurses. This study aimed to examine the influence of organizational commitment, effective communication, and the work environment on nurses’ caring behavior. A non-experimental, cross-sectional research design was employed. The analysis focused on measuring the extent to which independent variables affect the dependent variable. Data were analyzed using Multiple Linear Regression with the assistance of statistical software. Data collection was conducted through questionnaires distributed to inpatient nurses at Annisa Hospital Cikarang. The study population consisted of 95 nurses, with a final sample of 49 respondents. The statistical analysis was carried out using SPSS Version 24.0. The findings revealed that: (1) organizational commitment significantly influenced caring behavior (t = -2.751, p = 0.009 < 0.05); (2) effective communication significantly influenced caring behavior (t = 2.181, p = 0.034 < 0.05); (3) the work environment significantly influenced caring behavior (t = 3.365, p = 0.002 < 0.05); and (4) organizational commitment, effective communication, and the work environment collectively had a significant effect on caring behavior (F = 91.364, p = 0.000 < 0.05). In conclusion, organizational commitment, effective communication, and the work environment together account for 85.9% of the variance in nurses’ caring behavior, while the remaining 14.1% is explained by other factors not examined in this study. It is therefore recommended that reinforcement strategies be implemented to strengthen nurses’ caring behavior, particularly in inpatient care settings, by enhancing organizational commitment, improving communication effectiveness, and optimizing the work environment to foster positive caring practices.